RELATIONSHIP BETWEEN SELF ESTEEM WITH TENDENCY TO DATING VIOLENCE THE STUDENTS REGULAR 1 AND REGULAR 2 CLASS OF 2009 IN INDUSTRIAL ENGINEERING FACULTY DIPONEGORO UNIVERSITY - M., Trias Wulan; NRH, Frieda; Desiningrum, Dinie Ratri (Empati, 2013)
Based on teen dating phenomenon, a lot happened dependence on their partners. Dependency here means emotionally dependent and always never dared to resist what it wants partner and fear of abandonment. Dating process can lead to positive effects and negative effects. One of the negative effects is dating violence. This study aims to determine the relationship between self esteem with tendency to dating violence students in Industrial Engineering Faculty in Diponegoro University.In the study population were regular students regular 1 and regular 2 class of 2009 majoring in Industrial Engineering Faculty Diponegoro University. Sample was90 persons obtained through cluster random sampling technique. Retrieval of data using propensity scale violence in courtship consisting of 29 aitem (Î± = 0,952) and self esteem scale consisting of 37 aitem (Î± = 0,950).Processing the data using Non Parametric Method Statistical Test Spearman Rank Correlation Coefficient, rxy = -0,434 obtained with a significance level of 0,000 (p<0,05). The existence of a negative sign on the correlation coefficient indicates the direction the relationship is negative meaning that the highet the tendency of self esteem in dating violence has declined. Conversely, the lower the self esteem then making trend in dating violence is increasing.